SV 2021
DOI: 10.22514/sv.2021.130
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis for the epidemiological surveillance of COVID-19 in Chile

Abstract: Background: The emergence of COVID-19 so far and in the immediate future has brought significant uncertainties that negatively impact institutions and individuals in developing and planning their activities worldwide. The uncertainty of the effectiveness of vaccines has forced the authorities to adopt different protocols, the most relevant of which is the isolation of people through quarantine to avoid contagion, drastically affecting our way of life. For this reason, it is crucial to evaluate the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…22,23 In addition, Tanshinone IIA (Tan IIA) could improve sepsis-induced ALI by mediating ROCK2-NF-κB axis. 24 These studies, together with our findings, confirmed that NF-κB pathway could serve as a target for treating ALI.…”
Section: Competing Interestssupporting
confidence: 83%
“…22,23 In addition, Tanshinone IIA (Tan IIA) could improve sepsis-induced ALI by mediating ROCK2-NF-κB axis. 24 These studies, together with our findings, confirmed that NF-κB pathway could serve as a target for treating ALI.…”
Section: Competing Interestssupporting
confidence: 83%
“…The structure of this paper is organized as follows: Section 2 provides a concise description of the data used in this study, with a focus on the instantaneous reproductive number index generated in studies by [ 9 ]. We also explain the methods related to estimating the mean and median of the residual time until the control or non-control of the pandemic occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of COVID-19 was so rapid that almost all countries imposed either partial or complete lockdown in affected areas to curb its spread ( Li et al, 2021 , Ospina et al, 2021 ). Precautionary measures imposed by different governments are directing their masses to follow the standard operating procedure to control its spread ( Jerez-Lillo, Álvarez, Gutiérrez, Figueroa-Zúñiga, & Leiva, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…By the end of 2021, the COVID-19 disease infected almost 300 million persons and claimed the lives of more than five million of them worldwide. Both international authorities (such as the WHO) and governments have proposed the implementation of several measures to slow down the virus’s spread ( Jerez-Lillo et al, 2021 ). Among others, avoiding public transportation overcrowding has been pointed out as a relevant safety measure to implement.…”
Section: Introductionmentioning
confidence: 99%